TANGGUNG JAWAB NOTARIS ATAS AKTA AUTENTIK YANG DIBUATNYA DENGAN SURAT KUASA YANG CACAT HUKUM SERTA TIDAK DIBACAKANNYA AKTA TERSEBUT (STUDI KASUS PUTUSAN NOMOR 25/PDT.G/2017/PN.CBI) - Eric Sandro; Tjempaka Tjempaka (Jurnal Hukum Adigama, 2019)
At this time the need for Notary services is increasing, especially related to legal actions that are Private Law. Legal actions carried out by the parties concerned are usually set forth in an agreement made by the parties themselves and to be more binding on these legal actions the parties usually make an agreement in an authentic deed made by the competent official, the Notary. In exercising his office, a Notary shall also have the obligation to act in a trustworthy, honest, fair, independent, non-partisan manner and to safeguard the interests of the parties involved in a legal action. A Notary when carrying out his position is obligated to make certain that what is written in a notary deed is understood by the parties and the notary deed is written accordance to the parties’s desire. A Notary must always be responsible for any mistakes that was made by the Notary especially if the mistakes caused a material loss to its clients.